2021
DOI: 10.1186/s13567-021-00954-6
|View full text |Cite
|
Sign up to set email alerts
|

The spike glycoprotein genes of porcine epidemic diarrhea viruses isolated in China

Abstract: The porcine epidemic diarrhea virus (PEDV) causes a highly contagious disease in pigs, which is one of the most devastating viral diseases of swine in the world. In China, PEDV was first confirmed in 1984 and PEDV infections occurred sporadically from 1984 to early 2010. From late 2010 until present, PEDV infections have swept every province or region in China. In this study, we analyzed a total of 186 full-length spike genes and deduced proteins of all available complete genomes of PEDVs isolated in China dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Interestingly, an immunogenicity analysis showed that rAJ1102-S2′ JS2008 induced neutralizing antibodies against both PEDV strains AJ1102 and JS2008. Epidemiological investigations have indicated that G2 variants are the predominant PEDV strains in circulation, but the classical G1 strains are still present and circulating in China and other countries (42,43). Therefore, rAJ1102-S2′ JS2008 may be an important alternative novel vaccine strain because it simultaneously provides protection against both G1 and G2 PEDV infections.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an immunogenicity analysis showed that rAJ1102-S2′ JS2008 induced neutralizing antibodies against both PEDV strains AJ1102 and JS2008. Epidemiological investigations have indicated that G2 variants are the predominant PEDV strains in circulation, but the classical G1 strains are still present and circulating in China and other countries (42,43). Therefore, rAJ1102-S2′ JS2008 may be an important alternative novel vaccine strain because it simultaneously provides protection against both G1 and G2 PEDV infections.…”
Section: Discussionmentioning
confidence: 99%
“…The antigenic epitopes inducing neutralizing antibodies against PEDV infection in pigs are mainly located in the S glycoprotein. The mutations therefore more frequently occur in the S protein of PEDV [ 40 , 41 , 42 ]. Mutations in the S protein can lead to a variety of structural and functional consequences and contribute to the lack of efficacy of PEDV vaccines [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Porcine epidemic diarrhea virus (PEDV) is a novel virus that causes severe enteric disease in pigs; it belongs to the genus Alphacoronavirus [ 1 ]. The spread of PEDVs in pigs occurs via the oral–fecal route as well as through feeding and aerosol transmission [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%